MLS Observations of CIO and HNO 3 in the 1996-97 Arctic Polar - Santee, M. L.; Manney, G. L.; Froidevaux, L.; Zurek, R. W.; Waters, J. W. (2004)
Microwave Limb Sounder (MLS) measurements of lower stratospheric ClO and gas-phase HNO 3 are presented for the 1996-97 Arctic winter.